Quand l’agriculture prend de la hauteur. Filmer au jardin potager sur le toit de la clinique Pasteur à Toulouse - Olivier Bories (Éditions en environnement VertigO, 2018)
With the proliferation of urban agriculture operations the city is more gardened and more fertile. These operations usually take up ground spaces spared by artificialization. Some, more strangely, seize new ground in the basement or on the roofs. All of them show us a new way of making urban space, by preserving fertile land and by conquering new land underground or at a height. If Paris is a leader in supporting this type of innovative agri-urban project, it is in Toulouse and on the roof of a building of the Pasteur Clinic that there is the largest French hanging garden. It is this case of urban agriculture and this strangeness of a piece of countryside in the city that we studied. We have mainly filmed it to several researchers and interdisciplinary within the framework of a research program associating the UMR LISST Rural Dynamics and the Pasteur Clinic. In this work of research and filmic writing we questioned space. We focused on the geographic proximity of the city and the countryside, questioning the small area and the filling agriculture, the border and the spatial hybridization, the circulation and the mobility. We have also shown the social rapprochement, that of women and men, caregivers, administrative and technical staff who are gardening up there. They meet there, they meet there. They share the fantasy of the countryside and they find the opportunity to exchange emotions and pleasure. With the movie-search "Lift for the kitchen garden" we really propose to enter the kitchen experience and report on it.